Demonstrating the Reliability of the Self-Appraisal Questionnaire for Use With South African Offenders - Prinsloo, Johan (International criminal justice review, 2022)
The objective of this research was to examine the reliability and effectiveness of the Self-Appraisal Questionnaire (SAQ) for use with South African offenders. A total of 986 male offenders, with a mean age of 30.6 years (SD = 9.83) and who were incarcerated in different correctional centers in South Africa, participated in the study. Approximately 75% of the participants were convicted of violent crimes. The Cronbach’s α reliability coefficient for the total SAQ was .92 and subscale coefficients varied between .32, which are consistent with previous international results. Most of the inter-subscale correlations are statistically significant and of moderate strength (r = .4–.7) or small relationships (r = .2–.4). With a single exception, all the items-subscale correlations were above .30 and consistent with the results of prior research conducted in Australia, Canada, England, Singapore, and the United States of America.